Time-Domain and Spectral-Domain Optical Coherence Tomography of Retinal Nerve Fiber Layer in MS Patients and Healthy Controls - Alex P. Lange; Reza Sadjadi; Jameelah Saeedi; Janette Lindley; Fiona Costello; Anthony L. Traboulsee (Journal of Ophthalmology)
Objective. The aim of this study was to compare retinal nerve fiber layer thickness (RNFLT) between spectral-domain (SD-) and time-domain optical coherence tomography (TD-OCT) in MS patients and healthy controls (HC). Furthermore, RNFLT between MS eyes with and without optic neuritis (ON) and HC should be explored. Finally, the relationship between RNFLT, disease duration, EDSS, and disease modifying therapy (DMT) should be established. Design. Prospective, cross-sectional study. Participants. 28 MS patients and 35 HC. Methods. Both groups underwent TD- and SD-OCT measurements. RFNLT was correlated between the two machines and between MS eyes with and without ON and HC. Furthermore, RNFLT was correlated to disease duration, EDSS and DMT. Results. A strong correlation (Pearson’s r=0.921, P<0.001), but a statistically significant difference of 2 μm (P<0.001), was found between the two devices. RNFLT was significantly different between MS eyes with history of ON (mean RFNLT (SD) 72.21 μm (15.83 μm)), MS eyes without history of ON 93.03 μm (14.25 μm), and HC 99.07 μm (7.23 μm) (P<0.001). Conclusions. The measurements between different generation of OCT machines are not interchangeable, which should be taken into account if comparing results between different machines and switching OCT machine in longitudinal studies.